Innowacje we współzarządzaniu rozwojem regionalnym. Praktyka instytucjonalna w wybranych regionach w Polsce - Wiktorska-Święcka, Aldona; Klimowicz, Monika; Michalewska-Pawlak, Małgorzata (Oficyna Wydawnicza ASPRA, 2017)
The book was prepared within the framework of the research project “Innovations in regional governance in Poland” was financed by the National Science Centre as part of the research grant no. UMO-2013/09/B/HS5/04522. The issues presented in the book focus on model aspects of research on the innovation in regional governance. These include the following: actors involved in regional governance, decision-making processes and policy effects. The constructed model was used to carry out for empirical research on specific case studies of innovation in regional governance in Poland. In addition, the book contains the characteristics of the assumptions of theory of change in relation to the evaluation of the effects of intervention of innovative solutions in the area of regional governance. It also points to the key assumptions of the process tracing method, which was then used to analyse causal relationships between innovations and positive changes in regional governance that have followed their implementation. The analyses are conducted in the following thematic areas: metropolitan governance, rural governance and entrepreneurship development.
Keywords: innovations in regional governance; innovation; regional governance; process tracing; LEADER; Integrated Territorial Investment; entrepreneurial discovery process